ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR TETES TEBU DI INDONESIA 2012-2018 - Juliarta, I Wayan; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Molasses is one of the waste products resulting from processing sugar cane that cannot be crystallized anymore and still contains sugar. This study aims to analyze US Dollar exchange rate, price, and the amount of domestic sugarcane production simultaneously and partially on export volume of molasses in Indonesia 2012-2018. Data used secondary data, analysis multiple linear regression. The results is US Dollar exchange rate has significant negative effect on export volume of molasses in Indonesia 2012-2018. The price has a significant positive effect on export volume of sugarcane drops in Indonesia 2012-2018 and the variable amount of domestic sugarcane production has no effect the export volume of sugarcane drops in Indonesia 2012-2018. Simultaneously, US Dollar exchange rate, the price, and the amount of domestic sugarcane production have significant effect on the export volume of molasses in Indonesia 2012-2018 and the variable amount of domestic sugarcane production has no effect on the export volume of sugarcane drops in Indonesia 2012-2018. In this analysis, variable has dominant influence on the export volume of sugarcane drops in Indonesia 2012-2018 is the price variable.   Key words: US Dollar exchange rate, price, amount of domestic production, export volume of molasses in Indonesia